2018
DOI: 10.1097/ogx.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pregnancy Loss Evaluation Combined With 24-Chromosome Microarray of Miscarriage Tissue Provides a Probable or Definite Cause of Pregnancy Loss in Over 90% of Patients

Abstract: (Abstracted from Human Reprod 2018;33:579–587) Recurrent pregnancy loss (RPL) occurs in up to 4% of reproductive age couples. The American Society for Reproductive Medicine (ASRM) issued a guideline on the evaluation of RPL in 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…High frequency of chromosomal abnormality is generally appreciated as a cause of infertility and miscarriage in advanced maternal age 2,8 . The frequency of each chromosomal aneuploidy was previously investigated by several methods 2,6‐10 . The interpretations demonstrated that chromosomes 16, 22, X, 21, and 15 tended to be frequently aneuploid, and our data are consistent with these previous results (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…High frequency of chromosomal abnormality is generally appreciated as a cause of infertility and miscarriage in advanced maternal age 2,8 . The frequency of each chromosomal aneuploidy was previously investigated by several methods 2,6‐10 . The interpretations demonstrated that chromosomes 16, 22, X, 21, and 15 tended to be frequently aneuploid, and our data are consistent with these previous results (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, cell culture failure or maternal cell contamination often occurs, which are significant obstacles for the analysis 3‐5 . Currently, molecular cytogenetic approaches, such as array comparative genome hybridization and next‐generation sequencing (NGS), have been introduced for comprehensive chromosomal analysis 3,4,6 . Among them, NGS has attracted attention as an accurate, high‐resolution, and high‐throughput method and is expected to be applicable for chromosomal analysis of products of conception (POC) from spontaneous abortion 7‐10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome sequencing studies have shown that in up to 12% of couples with RPL, one of the parents is a carrier of a balanced chromosomal aberration, but chromosomal rearrangements are cryptic in up to 40% of cases, and, therefore, undetectable by karyotype analysis [19]. High resolution copy number analysis may aid in detection of cryptic chromosomal imbalances in RPL [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…RPL is a multifactorial condition that needs a stratified approach. Initial stratification can now occur using micro-array analysis of miscarried tissue thereby dividing RPL management into the loss of normal and abnormal pregnancies (4). There is a distinct lack of efficacious therapeutic options because of failure of adequate stratification to distinguish these in published studies.…”
Section: Treating Immunologic Aspects Of Recurrent Pregnancy Lossmentioning
confidence: 99%